Comprehensive approach for improving adherence to prenatal Iron and folic acid supplements based on intervention studies in Bangladesh, Burkina Faso, Ethiopia, and India - Sanghvi, Tina; Nguyen, Phuong Hong; Forissier, Thomas; Ghosh, Sebanti; Zafimanjaka, Maurice G.; Walissa, Tamirat Tafesse; Mahmud, Zeba; Kim, Sunny S. (SAGE Publications, 2023)
The World Health Organization recommends daily iron and folic acid (IFA) supplementation during pregnancy, but consumption remains low, and high prevalence of anemia among pregnant women (PW) persists.This study aims to (1) examine factors at the health system, community, and individual levels, which influence adherence to IFA supplements; and (2) describe a comprehensive approach for designing interventions to improve adherence based on lessons learned from 4 country experiences.We conducted literature search, formative research, and baseline surveys in Bangladesh, Burkina Faso, Ethiopia, and India and applied health systems strengthening and social and behavior change principles to design interventions. The interventions addressed underlying barriers at the individual, community, and health system levels. Interventions were further adapted for integration into existing large-scale antenatal care programs through continuous monitoring.Key factors related to low adherence were lack of operational protocols to implement policies, supply chain bottlenecks, low capacity to counsel women, negative social norms, and individual cognitive barriers. We reinforced antenatal care services and linked them with community workers and families to address knowledge, beliefs, self-efficacy, and perceived social norms. Evaluations showed that adherence improved in all countries. Based on implementation lessons, we developed a program pathway and details of interventions for mobilizing health systems and community platforms for improving adherence.A proven process for designing interventions to address IFA supplement adherence will contribute to achieving global nutrition targets for anemia reduction in PW. This evidence-based comprehensive approach may be applied in other countries with high anemia prevalence and low IFA adherence.